Orthodontic management of a case of Class III malocclusion with multiple unerupted teeth in both jaw & retained deciduous teeth : A case report (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
We describe the treatment of an adolescent girl, age 13 years old, with Class III malocclusion withnmultiple unerupted teeth in both jaw & retained deciduous teeth. Treatment consists mainly of correction of anterior crossbite, extraction of deciduous teeth, surgical exposure of unerupted teeth &orthodontic traction to help eruption, leveling and alignment with Edgewise fixed appliances with multiloop technique. Treatment time required 3years. However the treatment resulted in Class I molar occlusion with proper alignment of  upper & lower anterior segment, an ideal overjet, overbite andincisor angulations.Ban J Orthod & Dentofac Orthop, April 2013; Vol-3, No.2